An Analytical Study of Iraq's Participation in the Olympic Swimming Championships for the Period 1956-2016 - Zahia Sabah Abdulsalam (Journal of Global Pharma Technology, 2016)
The Problem of Research is to answer the Following QuestionsIs there a comprehensive historical study of all of Iraq's participation in the Olympic Games in swimming sport since the founding of the Iraqi Federation in 1956 and until 2016?Is there a study that presented the most important achievements achieved by Iraq in the sport of swimming during the Olympic Games for the period 1956 to 2016?Detecting the reasons that hindered Iraq's access to advanced positions in the Iraqi Olympic Swimming during the participations.Are there any reasons why Iraq did not participate in the sport of swimming in some Olympic Games during the period 1956 to 2016?The Research Objectives toRecognition of Iraq's participation in the sport of Olympic swimming in the Olympic Games since the founding of the Iraqi Federation in 1965 until 2016.Recognize the most important achievements achieved by Iraq in the sport of Olympic swimming in the Olympic Games during the period from 1965 to 2016.Identify the main obstacles that prevented Iraq from participating in some of the Olympic Games in this sport.The researchers discussed the history of the Iraqi swim and the presentation of all the Olympic Games since the emergence of the first session until 2016, whether there was a participation of Iraq in that session or not, and used the historical approach or so-called documentary methodology, benefiting from the analysis and discussion of all Iraq's foreign participation in the courses The research community represents the pioneers, swimmers, trainers and members of the current governing bodies of the Iraqi Central Swimming Federation, who have witnessed all the participations from 1956 to 2016 in the spa. The study sample consisted of (60) persons, (50) persons are the sample of the main experiment, and (10) people were the sample of the pilot experiment.The Researchers Concluded the Following:Most of Iraq's participation in the courses was very modest or weak.Decrease in the number of swimmers participating in modern courses due to economic and administrative reasonsLack of adequate infrastructure for swimmers as well as lack of material resources provided to swimmers by previous and current federations and for various conditions as well.The fluctuation in the previous years and for several reasons.The lack of material resources for holding special training camps prior to participation in the courses and if they are rare, they do not fit in with the number of courses held and participating in them.Keywords: Analytical study and Olympic Swimming.